A public library cannot live on books alone: A lesson from history. (March 2019) - Şerbănuţă, Claudia
For almost half a century Romania was under a totalitarian regime. In times of severe censorship and information control the communist regime promoted public libraries. This paper will present the main phases of the public library system development and discuss how the state's emphasis on providing large collections of books influenced library services. As part of an oral history project, this paper will use memories of people who worked in public libraries of various sizes in the 1970s and the 1980s, archival documents and secondary sources to contribute to a more nuanced discussion about the recent history of Romanian public libraries. What were the phases of the development of the national library system and how important was the library collection for the institutional survival of the public library? The paper will also discuss the collection development policy and contrast it with the impoverished professional development within the library system.